2017
DOI: 10.3390/rs9121208
|View full text |Cite
|
Sign up to set email alerts
|

Online Global Land Surface Temperature Estimation from Landsat

Abstract: This study explores the estimation of land surface temperature (LST) for the globe from Landsat 5, 7 and 8 thermal infrared sensors, using different surface emissivity sources. A single channel algorithm is used for consistency among the estimated LST products, whereas the option of using emissivity from different sources provides flexibility for the algorithm's implementation to any area of interest. The Google Earth Engine (GEE), an advanced earth science data and analysis platform, allows the estimation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(84 citation statements)
references
References 43 publications
2
66
0
Order By: Relevance
“…Imja Lake might significantly exceed the 4 • threshold in some September and early October measurements, but for the most part it also remains near or below 4 • C. Satellite-based observations were sparse during the summer monsoon due to the presence of cloud cover but generally show a plateau or depression of temperatures during the monsoon (Figure 4B). Lake temperature comparisons between ASTER and Landsat thermal data had an RMSE (mean difference) of 1.1 • C (Figure 4D), which is comparable to the RMSE of 1.52 • C (between ASTER and Landsat sensors) found by Parastatidis et al (2017) for land surfaces. ASTER might be more accurate as temperature is derived from five bands, instead of two for Landsat 8, but Landsat 8 gives a much better frequency of measurements.…”
Section: Satellite Surface Temperature Measurementssupporting
confidence: 69%
See 1 more Smart Citation
“…Imja Lake might significantly exceed the 4 • threshold in some September and early October measurements, but for the most part it also remains near or below 4 • C. Satellite-based observations were sparse during the summer monsoon due to the presence of cloud cover but generally show a plateau or depression of temperatures during the monsoon (Figure 4B). Lake temperature comparisons between ASTER and Landsat thermal data had an RMSE (mean difference) of 1.1 • C (Figure 4D), which is comparable to the RMSE of 1.52 • C (between ASTER and Landsat sensors) found by Parastatidis et al (2017) for land surfaces. ASTER might be more accurate as temperature is derived from five bands, instead of two for Landsat 8, but Landsat 8 gives a much better frequency of measurements.…”
Section: Satellite Surface Temperature Measurementssupporting
confidence: 69%
“…To calculate the mean lake temperature for each image, we applied an internal buffer of 150 m to the lake boundaries and used the remaining pixels in the lake interior to derive the lake temperature, excluding any pixels containing icebergs. We also used the thermal infrared bands of Landsat 5, 7 and 8, which generally had a slightly earlier acquisition time compared to ASTER (∼30 min earlier), to derive lake temperatures 2000-2018 using the Google Earth Engine (GEE)based Landsat Land Surface Temperature tool (Parastatidis et al, 2017). The tool used a single channel algorithm applied to thermal infrared data and includes atmospheric and emissivity corrections, and the application of a cloud mask.…”
Section: Satellite Measurements Of Lake Temperaturementioning
confidence: 99%
“…We topographically corrected the images and calculated the tasseled cap transformation to derive "brightness", "greenness", and "wetness" using sensor-specific coefficients [59,60]. Additionally, we derived the Normalized Difference Vegetation Index (NDVI, [61]) and downloaded the NDVI-based land surface temperature (LST) for each acquisition date [62].…”
Section: Satellite Remote Sensing Datamentioning
confidence: 99%
“…We hypothesized that the use more imageries produces clearer output images to understand the LST patterns in the study area. Past studies have shown the aptness of this method to generate LST in different areas [39] [40]. All extracted images were georectified using the WGS84/UTM 44N projection system before further processing.…”
Section: Mountain Cities In Asia Have Been Developing Since the Colonmentioning
confidence: 99%
“…The use of more satellite images captured in multiple time point can potentially provide more specific information to understand the changing pattern of LST [4]. Still, it is not easy to analyze extensive earth observation data set due to spatial and temporal resolution [39] [40]. Thus, big data analysis platforms can be used as an alternative for conducting accurate result [39].…”
Section: Introductionmentioning
confidence: 99%